2017
DOI: 10.3345/kjp.2017.60.9.296
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytokine expression profiles in infants with a rhinovirus induced lower respiratory tract infection with or without wheezing: a comparison with respiratory syncytial virus

Abstract: PurposeThe aim of this study was to evaluate whether infants with rhinovirus (RV) infection-induced wheezing and those with respiratory syncytial virus (RSV) infection-induced wheezing have different cytokine profiles in the acute stage.MethodsOf the infants with lower respiratory tract infection (LRTI) between September 2011 and May 2012, 88 were confirmed using reverse transcription polymerase chain reaction and hospitalized. Systemic interferon-gamma (IFN-γ), interleukin (IL)-2, IL-12, IL-4, IL-5, IL-13, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Compared with RSV infection, HRV-C induced relatively low cytokine secretion (except IFN-λ1 and IP-10) in response to HBE ALI cells during 48 h in this study. This is in accordance with previous clinical studies [ 17 , 18 ]. Unlike RSV, HRV does not determine airway epithelial cell a clear cytopathic effect but compromises the epithelial barrier function by dissociating zonula occludens-1 of the cells from the tight junction complex during viral replication [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…Compared with RSV infection, HRV-C induced relatively low cytokine secretion (except IFN-λ1 and IP-10) in response to HBE ALI cells during 48 h in this study. This is in accordance with previous clinical studies [ 17 , 18 ]. Unlike RSV, HRV does not determine airway epithelial cell a clear cytopathic effect but compromises the epithelial barrier function by dissociating zonula occludens-1 of the cells from the tight junction complex during viral replication [ 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…Compared with RSV infection, HRV-C induced relatively low cytokine secretion (except IFN-λ1 and IP-10) in response to HBE ALI cells during 48 hours in this study. This is in accordance with previous clinical studies [17,18]. Unlike RSV, HRV does not determine airway epithelial cell a clear cytopathic effect but compromises the epithelial barrier function by dissociating zonula occludens-1 of the cells from the tight junction complex during viral replication [19].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, regarding the change in the cytokine response from PBMCs, the RV group was characterized by a decreasing trend of Type 2-associated profile (I-309 and TARC) and an increasing trend of Type 1- and Th17-associated profiles (fractalkine and IL-1β, respectively). Although previous studies (from nasal swabs) have shown differences in IFN-γ and IL-10 expression between children infected with RV and RSV ( 37 ), one recent study showed that this difference dissipated when RV-bronchiolitis and RSV-bronchiolitis are accompanied by wheezing ( 38 ). This finding is in line with our results.…”
Section: Discussionmentioning
confidence: 98%